Activated Nitrogen-Containing Metabolites of the Human Body in Respiratory Diseases. Generators and Generation (Part 1) - O.Ye. Abaturov; O.P. Volosovets; T.P. Borysova (Zaslavsky O.Yu., 2015)
This literature review outlines the history of the discovery of nitric oxide, considers the characteristics of nitric oxide synthases, presents current data about the activated nitrogen-containing metabolites of the human body in diseases of the respiratory system.